Effects of STEM Activities in Nature on Students' Environmental Attitudes, STEM Career Interests, and Engineering Perceptions - Hasan Demir; Mücahit Kose (Journal of Education in Science, Environment and Health)
This study aimed to determine the effects of STEM Activities in Nature on students' environmental attitudes, STEM career interests, and engineering perceptions. In the research, the qualitative method is embedded in the quantitative method in an embedded mixed design. The quantitative dimension of the research was based on a quasi-experimental design with the pretest-posttest control group, and the qualitative dimension was based on a case study. The sample of the study consists of 74 seventh grade students from a moderate socio-economic level secondary school. In the study, STEM activities in the experimental group were carried out 2 hours a week for an 11-week period. In the control group, the activities were carried out in line with the Turkish Ministry of National Education's science applications course curriculum. According to the results of the research, STEM Activities in Nature in the experimental group positively affected students’ environmental attitudes and STEM career interests. The activities improved students' engineering perceptions.